2017
DOI: 10.1136/bjsports-2016-097372.248
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screen and Lower Limb Strength Asymmetry in Professional Soccer Players

Abstract: BackgroundThe Functional Movement Screen (FMS) protocol consists of 7 tests (Cook & Burton, 2014). At higher values mean higher quality of movement execution. Lower limb functional asymmetry (FA) is monitored to control the athlete's injury risk (Sannicandroet al., 2011).ObjectiveTo examine the correlation between the FMS score and strength asymmetry in professional soccer players (PSP).DesignDescriptive study (correlation study investigating the relationship between variables).SettingProfessional soccer.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…However, handgrip strength and the FMS scores do not seem to have clear connections [20]. Sannicandro et al [19] indicated that footballers presented better quality movement patterns that generated greater lower limb power. Willigenburg and Hewett [45] observed correlations between the length of the long jump and the overall FMS score among American football players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, handgrip strength and the FMS scores do not seem to have clear connections [20]. Sannicandro et al [19] indicated that footballers presented better quality movement patterns that generated greater lower limb power. Willigenburg and Hewett [45] observed correlations between the length of the long jump and the overall FMS score among American football players.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al [18] indicated the relationship between a trunk stability push-up with agility t-test result. Sannicandro et al [19] showed a connection between the FMS score and the power of the lower limbs among professional footballers, showing that better quality of movement patterns was associated with greater power of the lower limbs. Chimera et al [20] established strong relationships between flexibility and the trunk muscles' strength with movement patterns quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pre-season tests, football players presented smaller ranges of motion in the hip and knee joints they were more often injured during the season [ 22 ]. Literature reports indicate the relationship of lower limb power to injury [ 23 ]. It has been pointed out that a better ability to maintain balance is associated with fewer ankle injuries [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a relationship between physical performance and the quality of movement patterns [ 25 ]. Sannicandro et al [ 23 ] showed an association between better FMS scores and higher power of lower limbs among professional footballers. Chimera et al [ 26 ] showed strong links between flexibility and the quality of movement patterns and torso muscle strength.…”
Section: Introductionmentioning
confidence: 99%